Immuno-cardio-oncology: Killing two birds with one stone? - Van Linthout, Sophie; Volk, Hans-Dieter (Frontiers in Immunology, 2022)
Inflammation and a dysregulated immune system are common denominators of cancer and cardiovascular disease (CVD). Immuno-cardio-oncology addresses the interconnected immunological aspect in both cancer and CVD and the integration of immunotherapies and anti-inflammatory therapies in both distinct disease entities. Building on prominent examples of convergent inflammation (IL-1ß biology) and immune disbalance (CD20 cells) in cancer and CVD/heart failure, the review tackles both the roadblocks and opportunities of repurposed use of IL-1ß drugs and anti-CD20 antibodies in both fields, and discusses the use of advanced therapies e.g. chimeric antigen receptor (CAR) T cells, that can address the raising burden of both cancer and CVD. Finally, it is discussed how inspired by precision medicine in oncology, the use of biomarker-driven patient stratification is needed to better guide anti-inflammatory/immunomodulatory therapeutic interventions in cardiology.